Eksistensi Kontrak Kegiatan Ekonomi Kreatif Sebagai Jaminan Dalam Pengajuan Kredit Bank - Maulidya Ilhami; Lastuti Abubakar; Tri Handayani (Jurnal USM Law Review)
This research and article aim to find answers to the difficulties in implementing contracts for creative economy entrepreneurs as collateral, which are indeed regulated, but their implementation has never been carried out in Indonesia itself. The urgency of this research is to support the development of the creative economy industry sector, particularly in terms of funding, and to provide benefits and clarity for the parties involved. Therefore, legal research was conducted using the normative juridical method. This research and article provide new insights regarding contracts in creative economy activities as collateral, which have not been extensively discussed in previous literature. Based on the research conducted, it is known that, in principle, the regulation of contracts for creative economy entrepreneurs as collateral is very likely to be implemented as long as there is a specific mechanism regarding this matter. A mechanism is needed because a contract cannot simply be classified as an object, so the economic value contained in the contract can be guaranteed through fiduciary collateral. Furthermore, there is a need for regulations in the POJK regarding the details of the implementation of contracts by creative economy entrepreneurs as collateral, the approval of the parties involved in the contract related to the collateralization of the contract, and the application of the principle of prudence by banks before accepting creative economy activity contracts as collateral. With the existence of regulations and mechanisms, as well as the approval of the parties involved in using contracts from creative economy entrepreneurs as collateral, it can provide legal certainty in its implementation and protect the parties involved.